2018
DOI: 10.1002/syn.22058
|View full text |Cite
|
Sign up to set email alerts
|

Roux‐en‐Y gastric bypass surgery normalizes dopamine D1, D2, and DAT levels

Abstract: Roux-en-Y gastric bypass surgery (RYGB) is one of the most effective treatments for morbid obesity. However, increased substance abuse following RYGB has been observed clinically. This study examined the effects of RYGB on the dopamine system to elucidate these observed changes in reward-related behavior. Rats were assigned to four groups: normal diet with sham surgery, ad libitum high fat (HF) diet with sham surgery, restricted HF diet with sham surgery, and HF diet with RYGB surgery. Following surgeries, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 94 publications
(133 reference statements)
3
17
0
Order By: Relevance
“…While it is true that the major body of the RDS concept resides in many publications on the subject from our laboratory, there is an emerging increase in independent citations that embrace this novel construct. A brief sampling of this global cited work, while mostly favorable, can be assessed by reviewing specific references [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ,…”
Section: Introductionmentioning
confidence: 99%
“…While it is true that the major body of the RDS concept resides in many publications on the subject from our laboratory, there is an emerging increase in independent citations that embrace this novel construct. A brief sampling of this global cited work, while mostly favorable, can be assessed by reviewing specific references [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ,…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that MOR inhibition in the lateral hypothalamus, but not the nucleus accumbens or ventral tegmental area, reduces food intake in food-deprived mice, suggesting that opioid signaling in the hypothalamus mediates hunger rather than the rewarding aspect of food consumption [39]. Our laboratories previously reported that body weight significantly decreases in the 8 weeks following RYGB surgery [34] (Fig 3). The reduction in hypothalamus [ 3 H] DAMGO binding seen between the high-fat fed Sham-FR and RYGB groups suggests that decreased body weight may be due to decreased hunger driven by downregulated mu opioid signaling in this region.…”
Section: Discussionmentioning
confidence: 75%
“…We previously reported that dopamine receptor expression decreases in the nucleus accumbens and striatum of high-fat diet-fed rats, and returns to control levels following RYGB surgery [34]. Increased dopamine signaling in this region can facilitate reward-seeking behavior including food and drug intake [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In obese people, the availability of striatal dopaminergic D2R is reduced ( Wang et al, 2001 ), while several prefrontal cortex regions are overactivated upon meal consumption or exposure to food cues ( Tomasi and Volkow, 2013 ) (for review Volkow et al, 2011 ). Conversely, RYGB reduces prefrontal cortex activation and may restore striatal D2R availability ( Hamilton et al, 2018 ). In summary, postingestive sugar sensing is important for body homeostasis as well as sweet gustation, but the exact mechanisms underlying post-oral learned sugar preference still need to be elucidated.…”
Section: How Sugars Affect the Brainmentioning
confidence: 99%